Modeling and validation of photovoltaic thermoelectric flat plate collector (PV-TE-FPC). (1st February 2020) - Tiwari, Arvind; Alashqar, Omar Abdulaziz; Dimri, Neha
Highlights: The article is focused on the thermal modelling of PV-TEC-FPC water collector. The article is validating the thermal model developed. The article is first of its kind to attempt integration of PV-TEC-FPC water collector. Abstract: In this paper, a thermal model based on energy balance equations has been developed for photovoltaic thermoelectric flat plate collectors (PV-TE-FPC). The discussed PV-TE-FPC consists of a semitransparent PV module integrated with TE modules to increase the electrical efficiency and a tube-in-sheet arrangement placed below the TE modules for the flow of water and removal of thermal energy from the bottom surface of TE modules. The semitransparent PV module considered in the present study includes polyethylene terephthalate (PET) as the top and bottom cover material of the PV module, which offers the advantages of flexibility, transparent, thermal conductive. The developed thermal model has been experimentally validated by performing statistical analysis for fluid outlet temperature for the measured climatic parameters of Buraidah, Saudi Arabia in the months of February, March, and April 2019. The results illustrate a reasonable agreement between the theoretically calculated and experimental values.